Alpha-synuclein knockout impairs melanoma development and alters DNA damage repair in the TG3 mouse model in a sex-dependent manner - Arnold, Moriah R.; Chen, Suzie; Unni, Vivek K. (Frontiers in Oncology, 2025)
IntroductionStrong evidence suggests links between Parkinson’s Disease (PD) and melanoma, as studies have found that people with PD are at an increased risk of developing melanoma and those with melanoma are at increased risk of developing PD. Although these clinical associations are well-established, the cellular and molecular pathways linking these diseases are poorly understood. Recent studies have found a previously unrecognized role for the neurodegeneration-associated protein alpha-synuclein (αSyn) in melanoma; the overexpression of αSyn promotes melanoma cell proliferation and metastasis. However, to our knowledge, no studies have investigated the role of αSyn in in vivo melanoma models outside of a xenograft paradigm. MethodsOur study created and characterized Snca knockout in the spontaneously developing melanoma TG3 mouse line, TG3+/+Snca-/-. ResultsWe show that αSyn loss-of-function significantly delays melanoma onset and slows tumor growth in vivo in males. Furthermore, decreased tumor volume is correlated with a decreased DNA damage signature and increased apoptotic markers, indicating a role for αSyn in modulating the DNA damage response (DDR) pathway. DiscussionOverall, our study may suggest that targeting αSyn and its role in modulating the DDR and melanomagenesis could serve as a promising new therapeutic target.